ANALISIS HUKUM TERHADAP PENGAWASAN ANGGARAN BERBASIS KINERJA PADA KANTOR BAPPEDA PROVINSI SULAWESI TENGAH - Christien Linda Afrilianti (Fakultas Hukum Universitas Muhammadiyah Palu, 2017)
The research was to juridically analyze the implementation of budgeting control in Central Sulawesi Provincial Development Planning Agency and idenyify their job performance in case of manipulation inprovincial fund management. It was a normative research adopting juridical and conceptual approaches. The sources of date were primary and secondary. The results of the research showed 2 findings. (1) the control was applied during planing, implementation, management, reporting and acountability of the provincial budget. Such a step was preferable to prevent financial manipulation and losses since preventive measures agains financial manipulation were perceived to be better than currative ones. Having gained Reasonable Without Exception financial reporting predicate twice, the Central Provincial Goverment would be more encoraged to better prepare transparent and effective accrual-based financial accountability reports in order to be more consistent to good governance principle. (2) The performance was evaluated to identivity progresses in the programs and activities in order to gain indicators that the Agency was clean, transparent and accountable in the processes of fair and effective budgeting in consistent with the good governance principleKeywords : clean, transparent and accountable budgeting control, based ongood coorporate governance principle.